PENGARUH UKURAN PERUSAHAAN, UKURAN KAP, KLASIFIKASI INDUSTRI, DAN TINGKAT PROFITABILITAS PERUSAHAAN TERHADAP AUDIT DELAY (STUDI EMPIRIS PADA PERUSAHAAN YANG TERMASUK 50 MOST ACTIVE STOCKS BY TRADING VALUE TAHUN 2014-2016) - Misbahul Mun’im; Nur Diana; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2019)
AbstractEvery goes public company, is obliged to report financial statements periodically and on time no later than delivered on March 31 of the following year or at the end of the third month (90 days) after the annual financial reporting date. The audited annual report will be used as the basis for decision making for investors.The financial statements published by the issuer to the public must be audited financial statements by an independent Auditor, so that the time required by the Auditor to audit financial statements also influences the timely publication of the company's financial statements. In this study aims to determine the effect of Company Size, Size of Public Accounting Firms, Industrial Classification, and the Level of Company Profitability on the audit process (audit delay) Audit Delay on Companies Including 50 Most Active Stocks by Trading Value Year 2014-2016The analytical method used in this study is using multiple regression analysis through SPSS testing by considering the classic assumption test, namely normality, multicollinearity, heteroscedasticity and autocorrelation.The results of the study show that the size of the company, the size of the public accounting firm and the level of profitability do not affect audit delay, while the classification of industry has a significant influence on audit delay. Keywords :  Audit Delay, Company Size, Size of Public Accountant Office,Industrial Classification, and Level of Company Profitability